IDENTIFICATION OF THE SPREAD OF BORAX USE IN MEATBALL SKEWERS IN BANTUL DISTRICT, SPECIAL REGION OF YOGYAKARTA - Sabtanti Harimurti; Imelda Horirotul Bariroh; Asep Setiyawan; Ratna Indah Permatasari; Friccillia Dwi Putri; Leni Yasinta Fajriana (Sanata Dharma University, 2020)
Borax is an additive that is often added to some foods such as meatball skewers. The government has banned this ingredient from being added to food because it is harmful to health when consumed for a long time. This study aims to identify the use of borax in Bakso Tusuk or meatball skewers sold in Bantul area. Samples were drawn from 17 sub-districts in Bantul, Special Region of Yogyakarta. Two samples were taken from each sub-district, so the number of total samples was 34. The speed of decay test was carried out by observing the appearance of fungus, maggots, and consistency of the surface of meatball skewers. The presence of borax in the meatball skewers was done by turmeric paper and flame test, while the quantitative analysis utilized the acid-base titration method. Based on the results of the study, all samples tested positive for borax with concentrations between 0.06% - 5.15%, and the decay rate test showed that the speed of decay was independent of the level of borax.